Perceived teacher support, peer relationship, and university students’ mental health: The mediation of reality and Internet altruistic behaviors - Feng, Linlin; Zhang, Lelin (Frontiers in Psychology, 2022)
Studying in universities is a crucial development stage for students, whose thoughts, ideals, and actions are affected by interactions with their teachers and peers. This study explored the relationships between perceived teacher support and mental health as well as those between peer relationship and mental health among university students, and examined the mediating effects of reality and internet altruistic behaviors on these relationships. Perceived teacher support questionnaire, peer relationship satisfaction questionnaire, self-reported altruism questionnaire, internet altruistic behavior questionnaire, and general health questionnaire were administered to 553 university students. Results demonstrated that perceived teacher support and peer relationship positively predicted reality and internet altruistic behaviors and positively predicted mental health. Reality and internet altruistic behaviors positively predicted mental health and exerted significant mediating effects on the correlations between perceived teacher support and mental health as well as those between peer relationship and mental health. The male and female students differed insignificantly in the mediating effects of reality and internet altruistic behaviors. Therefore, teachers should provide sufficient support for the students and establish favorable relationships with them. Friendly relationships, tolerance, and active communication among students are also essential for creating a healthy and harmonious interaction environment. Those various factors of the school have impacts on the mental health of university students through altruistic behaviors. This study suggests that further emphasis on teacher support and peer relationship is needed to promote the positive development of altruistic behaviors among university students, and ultimately provide a viable contribution to the university students’ mental health interventions.